2013
DOI: 10.1542/peds.2012-1255
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Influenza in Young Children, 2004–2009

Abstract: OBJECTIVE: To characterize the health care burden of influenza from 2004 through 2009, years when influenza vaccine recommendations were expanded to all children aged ≥6 months. METHODS: Population-based surveillance for laboratory-confirmed influenza was performed among children aged <5 years presenting with fever and/or acute respiratory illness to inpatient and outpatient settings during 5 influenza seasons in 3 US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(81 citation statements)
references
References 35 publications
5
75
1
Order By: Relevance
“…During the 6 studied influenza seasons, we found that, while children under the age of 15 years have the highest ILI and MCIC rates, the very young (0‐4 years) and the elderly exhibit the highest rates of severe influenza‐associated hospitalizations. This is consistent with previous studies showing that young children and adolescents have the highest rates of medically attended influenza,7, 12, 13, 14 while the highest hospitalization rates for influenza are observed among very young15 and persons aged ≥65 years 16. Previous exposure to influenza viruses, providing a partial immunity to the circulating viruses, and higher vaccine coverage than in other age‐groups,17, 18 could account for the lower ILI rates at the primary care level in the elderly population.…”
Section: Discussionsupporting
confidence: 93%
“…During the 6 studied influenza seasons, we found that, while children under the age of 15 years have the highest ILI and MCIC rates, the very young (0‐4 years) and the elderly exhibit the highest rates of severe influenza‐associated hospitalizations. This is consistent with previous studies showing that young children and adolescents have the highest rates of medically attended influenza,7, 12, 13, 14 while the highest hospitalization rates for influenza are observed among very young15 and persons aged ≥65 years 16. Previous exposure to influenza viruses, providing a partial immunity to the circulating viruses, and higher vaccine coverage than in other age‐groups,17, 18 could account for the lower ILI rates at the primary care level in the elderly population.…”
Section: Discussionsupporting
confidence: 93%
“…Population‐based studies have shown that the actual burden of influenza in children is under‐recognized with common (ILI) surveillance methods. For example, between 2004/05 and 2008/09 Poehling conducted a population‐based study in three US counties and found that per season, between 10% and 25% of children aged 0‐4 years sought outpatient medical care because of influenza 15. Our estimates in these two age groups between the seasons 2002/03 and 2008/09 ranged from 2% to 17% (age group 0‐4; median 11%) and from 3% to 13% (age group 5‐14; median 8%), respectively, and are therefore comparable with the thoroughly conducted population‐based research study.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of influenza is inversely related to age, with 50% of influenza-related hospitalisations occurring in infants younger than 6 months of age [120,122]. Data from a wide population-based study of children under 5 years who were admitted to hospital or presented to outpatient clinic with an acute respiratory illness, over five influenza seasons, showed that 35% of hospitalised children and 7% of outpatient children had laboratory-confirmed influenza, despite the extended vaccination recommendations in the population studied [123]. The long-term impact of influenza-related respiratory illnesses during early life is largely unknown, particularly among preterm infants.…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%